Implementation of Technology-Based Learning to Improve the Professional Competence of Postgraduate Students in English Language Learning - Wardhono, Agus; Apriono, Djoko; Panggabean, Christina Innocenti Tumiar; Supiyanto, Yudi; Yuliasari, Ulfa (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study investigates the experiences and perceived meanings of implementing a technology-based Project-Based Learning (PjBL) model in English language education and its contribution to developing the professional competence of postgraduate students at Universitas PGRI Ronggolawe Tuban. Utilizing a qualitative phenomenological approach, the research adopts Colaizzi’s method to deeply analyze students’ lived experiences. The participants consisted of 25 postgraduate students enrolled in a zero-credit English course during the matriculation program of the 2024–2025 academic year. Data were collected through in-depth interviews, participatory observations, document analysis, and focus group discussions involving students, lecturers, and institutional records. Through Colaizzi’s seven-step data analysis, themes emerged highlighting significant improvements in students’ English proficiency, critical thinking, creativity, collaboration, and digital literacy. The technology-integrated PjBL approach fostered student engagement in authentic learning contexts while encouraging learner autonomy and responsibility. Additionally, the lecturer's role shifted to that of a facilitator, guiding students to take ownership of their learning processes. The study concludes that the integration of technology into PjBL not only supports effective language acquisition but also cultivates essential 21st-century competencies. These findings underline the holistic benefits of this approach in enhancing the academic and professional readiness of postgraduate students in English education.